2020
DOI: 10.1021/acsearthspacechem.0c00119
|View full text |Cite
|
Sign up to set email alerts
|

Proline Behavior in Model Prebiotic Peptides Formed by Wet–Dry Cycling

Abstract: The amino acid proline plays critical roles in polypeptide structure and function. However, the influence of proline residues on proto-peptide evolution is unknown. In order to begin exploring this question, we formed mixtures of model prebiotic peptides by wet–dry cycling and compared proline incorporation to that of glycine, alanine, and valine. Proline uptake was more efficient than the other amino acids into linear oligomers. However, proline was also found in small, cyclic species. In a more complex mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Many exciting studies have been reported by simulating prebiotic wet‐dry cycles. [ 64‐67 ] A representation of wet‐dry driven prebiotic peptide formation is shown in Figure 6. Briefly, water evaporation promotes the formation of peptide in the dry phase.…”
Section: Prebiotic Peptide Formationmentioning
confidence: 99%
“…Many exciting studies have been reported by simulating prebiotic wet‐dry cycles. [ 64‐67 ] A representation of wet‐dry driven prebiotic peptide formation is shown in Figure 6. Briefly, water evaporation promotes the formation of peptide in the dry phase.…”
Section: Prebiotic Peptide Formationmentioning
confidence: 99%
“…Model prebiotic molecules were generated from monomers by wet–dry cycling experiments and DKMs such as 61 identified in the obtained mixtures, in addition to depsipeptides, polyesters, peptides, and yet unreacted hydroxy and amino acids ( Scheme 13 ). 25 …”
Section: Chemical Reactivity and Utilization In Ring-opening Polymerizationsmentioning
confidence: 99%
“…The greater propensity of proline and N -methyl-substituted amino acids to adopt a cis conformation and the consequent preferred DKM cyclization might account for the more frequent appearance of bicyclic DKMs such as 61 ( Scheme 13 ) 25 and N -methyl-substituted DKMs such as 42 – 48 ( Figure 2 ).…”
Section: Natural Productsmentioning
confidence: 99%
“…The ubiquity of both water and condensation reactions in the prebiotic formation of biopolymers (as well as the necessity of water for life processes), the so-called water paradox ( 21 ), suggests highly specific conditions and/or the presence of robust and generalizable processes capable of facilitating such chemistry prior to the appearance of proto-enzyme catalysts. This point has been addressed through a variety of approaches which seek to explain the global or localized removal of water from a system to favor condensation ( 16 20 , 22 27 ).…”
mentioning
confidence: 99%